HADÎTS DLA’ÎF DAN KEHUJJAHANNYA (Telaah terhadap Kontroversi Penerapan Ulama’ sebagai Sumber Hukum) - Abdul Rokhim (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2009)
Hadits is the second argumentation (hujjah) source after al-Qur’ân. However, there are many hadits refused becoming as anargumentation. According to the perspective of a Hadîts whetherit is accepted or refused, it has three stages, namely shahîh,hasan, and dla’îf This article focuses on the discussion of Hadîtsdla’îf, its argumentation and also its telling. In this relationship,there are three arguments of ulama’ Hadîts related to theargument of Hadîts dla’îf . Firtsly, the argument states that Hadîtsdla’îf cannot be applied absolutely. Secondly, Hadîts dla’îf can beapplied absolutely. Thirdly, Hadîts dla’îf can be used in fadla’il alamah.In its telling, ulama hadits reminded people who tolddla’if Hadîts without sanad not to tell by redacting whichshowed full stability that it was a Hadîts.